Antibiotic Resistance in Salmonella: A Risk for Tropical Aquaculture - Costa, Renata Albuquerque; Carvalho, Fátima Cristiane Teles de; Vieira, Regine Helena Silva dos Fernandes (IntechOpen, 2012)
None